Marginalized Minority Groups In Europe In The Context Of The Clash Of Civilisations: The Case Of Muslims - Yardim, Muserref; Tecim, Erhan (European Scientific Journal, ESJ, 2016)
One of the most important issues faced by the European civilization is immigrants. These immigrants are not considered to be European, can be marginalized due to national-ethnic-religious reasons, and defined in the invisible European ’other’. This attitude is not rational at all for the European civilization and it is on the agenda of many European countries on the verge of the 21st Century. With political decisions taken and practices put into effect, the existing distinction is being clarified and efforts are exerted to make the increasing contrast extant. It has become quite a common situation for many European countries that individuals, especially politicians, coming to the agenda with clearly Eurocentric rhetorics, increase their popularity and serve to exclusionary rhetorics along with such popularity. The social category which is the basic object of such an action again becomes the emigrating citizens of Muslim countries which were included in the colonization movements a few centuries before as well as the people of Muslim countries who were invited to European countries by the latter due to the labour needs. In addition to passing of at least 70 years since they were recruited as labour force, the third and fourth generation Muslims have preferred to remain as citizens in several European countries. It should be emphasized that social and political issues started at this point. It is a pleasing and rational development for harmony and coexistence that those people who were once regarded as religious minorities or Muslim minorities are beginning to have a voice. Yet, it needs emphasizing that this situation is unacceptable in most cases, national policies complicate harmonization rather than facilitating, and a considerable part of the European countries subject them to otherisation due to their different ethnic and religious identity, and most importantly they are not accepted in European countries.